The role of nurses in care for pregnant with diabetes mellitus (Research, Society and Development, 2022)
Introduction: Gestational diabetes affects about a quarter of pregnant women around the world. The nurse has an important role in monitoring this pathology, as he/she monitors the pregnant woman's prenatal care, thus being able to identify the onset of gestational diabetes and forward her to high-risk prenatal care offering care support still bigger. Objective: To describe the role of nurses in assisting pregnant women with gestational diabetes mellitus. Methodology: This is an integrative literature review carried out in the MEDLINE, LILACS, BDENF databases, with articles from the last five years, in Portuguese, English and Spanish. Results: In the articles selected for the final sample, we can highlight that the nursing staff works in the collection and identification of blood glucose changes, during prenatal care, they can identify and refer the pregnant woman to risk prenatal care. and medicate under medical prescription in order to reduce blood glucose levels, guide changes in habits and nutrition to prevent GDM, act during emergency childbirth providing care to the mother and newborn, guide healthier habits in the postpartum period in order to avoid a future WID. Final Considerations: The nurse works in the care of pregnant women with GDM, both in primary care where the problem is identified, and within high-complexity maternity hospitals, providing comprehensive care to the mother and newborn. Avoiding possible complications and promoting better health conditions.